2018
DOI: 10.1556/2006.7.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Ten myths about work addiction

Abstract: Background and aims Research into work addiction has steadily grown over the past decade. However, the literature is far from unified and there has been much debate on many different issues. Aim and methods This paper comprises a narrative review and focuses on 10 myths about work addiction that have permeated the psychological literature and beyond. The 10 myths examined are (a) work addiction is a new behavioral addiction, (b) work addiction is similar to other behavioral addictions, (c) there are only psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
180
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(206 citation statements)
references
References 106 publications
(171 reference statements)
20
180
2
4
Order By: Relevance
“…First, through this study one of the essential aspects of workaholism, the compulsive dependence on work, is clearly replicated. As Robinson (1998) (Atroszko et al 2018;Griffiths et al 2018;Harpaz & Snir 2003;Quinones 2018). In the present study, the compulsiveness dimension of the WAQ, i.e., the "work addiction" factor in Aziz et al (2013), was well extracted as CD, if with different items correlated.…”
Section: Discussion and Implicationsupporting
confidence: 50%
“…First, through this study one of the essential aspects of workaholism, the compulsive dependence on work, is clearly replicated. As Robinson (1998) (Atroszko et al 2018;Griffiths et al 2018;Harpaz & Snir 2003;Quinones 2018). In the present study, the compulsiveness dimension of the WAQ, i.e., the "work addiction" factor in Aziz et al (2013), was well extracted as CD, if with different items correlated.…”
Section: Discussion and Implicationsupporting
confidence: 50%
“…Both addictions show seven core addiction symptoms: salience, mood modification, tolerance, withdrawal, conflict, relapse, and problems (Atroszko et al, 2015). Moreover, both of them are related to higher engagement in studying/working, longer time devoted to studying/ working, key personality traits (higher neuroticism and conscientiousness), lower performance levels, impaired general health, decreased quality of life, poor sleep, and higher perceived stress (Atroszko, 2015;Atroszko et al, 2015;Griffiths et al, 2018). Furthermore, study addiction and work addiction show similar prevalence rates, which are typically around 8-10% (Atroszko, 2015;Griffiths et al, 2018); however, some studies suggest higher rates in particular populations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both of them are related to higher engagement in studying/working, longer time devoted to studying/ working, key personality traits (higher neuroticism and conscientiousness), lower performance levels, impaired general health, decreased quality of life, poor sleep, and higher perceived stress (Atroszko, 2015;Atroszko et al, 2015;Griffiths et al, 2018). Furthermore, study addiction and work addiction show similar prevalence rates, which are typically around 8-10% (Atroszko, 2015;Griffiths et al, 2018); however, some studies suggest higher rates in particular populations. For example, the known prevalence rates based on a polythetic cut-off score of the Bergen Work Addiction Scale (which in the absence of the gold standard can be considered the most theoretically sound and empirically valid available cut-off) suggest 6.6% addicted in Denmark, 8.3% in a nationally representative sample in Norway, and 16.8% in Poland (Andreassen et al, 2014;Atroszko, Pallesen, Griffiths, & Andreassen, 2017;Lichtenstein, Malkenes, Sibbersen, & Hinze, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that a low level of job satisfaction is strongly associated with burnout, depression, anxiety, and low level of self-esteem [5]. Although there has been an increasing number of studies exploring the problem of excessive work and work addiction over the past 2 decades, contrary to other behavioral addictions, there are many unanswered questions related to the psychology of work addiction [6]. For instance, only a few studies have investigated the psychological antecedents of work addiction in a longitudinal context (see review by Clark et al [7]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the terms "workaholism" and "work addiction" have been used interchangeably in the literature. In the present study, only the term "work addiction" is used because this term is theoretically based on the core addiction literature, whereas workaholism typically refers to excessive working independently from its negative or positive consequences [6]. During the past 4 decades, several definition and conceptualization have been developed relating to work addiction [7].…”
Section: Introductionmentioning
confidence: 99%